Implementación de sistema de gestión por procesos en el departamento administrativo del futbol club INSUTEC - Viteri Villa, Xavier Danilo (2025)
The Process Management System at INSUTEC Football Club is an organizational approach aimed at optimizing and coordinating activities within the club through the identification and management of key processes. This system focuses on improving operational efficiency, service quality, and member satisfaction, including players, coaches, and administrative staff. The main objective of this article is to implement a process management system to enhance the work within the administrative department of INSUTEC Football Club. The type of research utilized was descriptive and field-based, and the methodology employed was both qualitative and quantitative, which allowed for an understanding of the club executives' evaluations regarding management and administrative processes. It is crucial to develop a comprehensive plan that includes ongoing training, documentation of processes, and clear success metrics to ensure that the implementation of the Process Management System is effective and sustainable over time. In summary, the Process Management System at INSUTEC Football Club is a strategy aimed at optimizing all aspects of the club to effectively and sustainably achieve its mission and vision, striving for sporting excellence within Ecuadorian football.